2020
DOI: 10.1021/acsami.0c06500
|View full text |Cite
|
Sign up to set email alerts
|

A Physically Triggered Cell Death via Transbarrier Cold Atmospheric Plasma Cancer Treatment

Abstract: Cold atmospheric plasma (CAP) is a near room-temperature ionized gas composed of highly reactive species. CAP also generates thermal radiation, ultraviolet radiation, and electromagnetic (EM) waves. So far, nearly all biological effects of CAP have relied on the chemical factors in CAP. Here, we first show that the EM emission from CAP can lead to the death of melanoma cells via a transbarrier contactless method. Compared with reactive species, the effect of the physical factors causes much stronger growth inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 31 publications
8
94
0
Order By: Relevance
“…Attesting to the significant role of CAP emitted electromagnetic waves, is was recently revealed that CAP could cause cell death even when a physical barrier was introduced between the cells and the CAP jet. However, the role of EM waves in CAP-TMZ treatment is yet to be investigated 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Attesting to the significant role of CAP emitted electromagnetic waves, is was recently revealed that CAP could cause cell death even when a physical barrier was introduced between the cells and the CAP jet. However, the role of EM waves in CAP-TMZ treatment is yet to be investigated 70 .…”
Section: Discussionmentioning
confidence: 99%
“…130 It is promising that we may see that many new unknows about the biological impact of bulk CAP, such as potential physical effect. 131,132…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…Another important reason for the stronger anti-tumor effect of direct CAP treatment could be physical. Next to RONS production, CAP also generates thermal-and ultraviolet (UV) radiation, which also have a strong impact on tumor cell behavior [54][55][56], and which are not available in the case of indirect treatment with PTS.…”
Section: Discussionmentioning
confidence: 99%